Optimization of medium components for hyrogen production of anaerobic bacterial strain Thermoanaerobacterium aciditolerans Trau DAt isolated from Vietnam by using response surface methodology - Yen, Nguyen Thi; Hien, Lai Thuy; Thu Huyen, Nguyen Thi (Academia Journal of Biology, 2014)
The 21st century is era of renewable energy in which biohydrogen is the most potential candidate that may replace the fossil fuel. Many countries pay more attention to biohydrogen since it can produce by bacteria via fermentation and gas-biosynthesis has many advantages. Bacterial strain Thermoanaerobacterium aciditolerans Trau DAt isolated from Vietnam is capable of biohydrogen production in anaerobic condition. The gas volume as well as the gas components produced by the strain Trau DAt depends on nutrient and fermentation conditions. Hydrogen production of strain Trau DAt was highly affected by glucose, yeast extract and FeSO4.7H2O. By using response surface methodology (RSM) with central composite design, the mutual effects of these factors on hydrogen production of strain Trau DAt were studied. RSM analysis showed that the highest hydrogen production potential (176.02 ml/150 ml culture medium) was obtained under the condition of glucose 12 g/l, yeast extract 2.5 g/l, FeSO4.7H2O 400 mg/l. Under optimized condition, the maximum H2 volume of 420 ml/600 ml culture medium was obtained by dark fermentation.